2020: A challenging but extraordinary year for science - Committee, Editorial (Austral Journal of Veterinary Sciences, 2021)
The past year marked the lives of many people around the world, not just those whose freedom was restricted or suffered the loss of a loved one, but all humanity. The COVID-19 pandemic produced by SARS-Cov-2 has shown once again that the constant expansion of the world’s population and the degradation of ecosystems expose us to new threats. This situation is far from new, and what is more worrying is that it has been predicted for some time by the scientific community ...